Random graphs '85 : based on lectures presented at the 2nd International Seminar on Random Graphs and Probabilistic Methods in Combinatorics, August 5-9, 1985 - Karonski, Micha; Palka, Zbigniew (North-Holland mathematics studies, 1987)
Covering a wide range of Random Graphs subjects, this volume examines series-parallel networks, properties of random subgraphs of the n-cube, random binary and recursive trees, random digraphs, induced subgraphs and spanning trees in random graphs as well as matchings, hamiltonian cycles and closure in such structures. Papers in this collection also illustrate various aspects of percolation theory and its applications, properties of random lattices and random walks on such graphs, random allocation schemes, pseudo-random graphs and reliability of planar networks. Several open problems that were presented during a special session at the Seminar are also included at the end of the volume.